Nanomaterial biocompatibility and antimicrobial effects on Escherichia coli - Sanober, Fahmi; Ahmad, Siti Khadijah; Wan Salim, Wan Wardatul Amani (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
The combination of biological technology and physical science in nanobiotechnology opens up a whole new world of biosensors with better specificity, functionality, and sensitivity. Utilization of carbon nanomaterials, e.g., carbon nanotubes (CNTs) and graphene oxide (GO), and metal nanoparticles, e.g., gold nanoparticles (AuNPs) and silver nanoparticles (AgNPs), has improved the performance of third-generation biosensors. Nanomaterials in electrochemical biosensors enable fast, selective, and sensitive pathogen detection. However, the relationship between transducer layer and responding cells needs to be understood. Employing nanomaterial on the biosensor transducer layer can significantly affect cell viability owing to cytotoxic and bactericidal properties. Therefore, we studied the response of E. coli to nanomaterials in biosensor development. E. coli were cultured with these nanomaterials separately in Luria-Bertani broth medium. Bacterial cell viability was measured every 2 hours for 12 hours. Biocompatibility and antimicrobial effects were observed and analyzed via the bacterial growth curves. In addition, bacterial cell dry weight was measured after 12 hours of incubation. In terms of biocompatibility and antimicrobial properties, the results clearly prove that CNTs, AgNPs, and AuNPs have bactericidal or antimicrobial properties. On the other hand, GO does not have intrinsic bactericidal, cytotoxic, and/or antibacterial properties and greatly enhances bacterial growth. These significant advances in our knowledge concerning the properties of carbon nanomaterials and metal nanoparticles can guide the selection of appropriate nanomaterials to fabricate the transducer layer of any biosensor.